Design and Analysis of Linear Connecting Rod Climbing Mechanism - Zhifang Zhu; Zhijie Zhang; Jiawei Pan; Zeping Zou; Bingliang Ye; Baoling Liu (Jixie chuandong)
Based on the comparison and analysis with the climbing mechanism of the existing electric wheelchair， the linear connecting rod climbing mechanism is proposed. The design research of linear connecting rod climb mechanism is carried out， the endpoint trajectory upper part as the semicircle， the approximate linear the lower part of the string， the trajectory and animal walking gait extremely similar， so use it as a climbing mechanism design basis， and by using the SolidWorks software climb straight connecting rod mechanism modeling， and during the process of climbing stairs trajectory of climbing mechanism is analyzed. The simulation results show that the design scheme of the climbing mechanism is reasonable， the climbing trajectory of the climbing mechanism is approximately linear， and the turbulence is greatly reduced， which provides a new theoretical reference for the design of the climbing mechanism.